Comparison Neutrophil to Lymphocyte Count Ratio with C-Reactive Protein as a Predictor for Neonatal Sepsis - Nugroho, Irfan Dzakir; Hidayah, Dwi; Salimo, Harsono (Indonesian Journal of Medicine, 2021)
Background: Accurate early detection of bacteriemia plays an important role in the treatment and prognosis of infected neonates, but is constrained by the limitations of specific sepsis markers for detecting bacteriemia. NLCR or neutrophil to lymphocyte count ratio in adult population shows a more sensitive parameter in predicting infection and has the advantage of being economical and widely available. The role of NLCR in the neonatal population has not been widely studied. The purpose of this study was to analyze NLCR versus CRP as a predictor of neonatal sepsis.Subjects and Method: This study take analytic observatinal with diagnostic test approach to subject with sepsis risk factor and neonatal sepsis at dr. Moewardi hospital from April until May 2017. Characteristics data as gestational age, gender, birth weight, IT ratio, leucocyte count, neutrophil and lymphocyte count, NLCR, CRP and blood culture. Data presented descriptively and statistical analysis was performed.Results: No significant correlation between subject’s characteristics and neonatal sepsis. NLCR with cutoff point for 2.22 has sensitivity, specificity, positive and negative predictive value for 87.5%, 75%, 70% and 90%, respectively. CRP with cutoff point for 0.25 has sensitivity, specificity, positive and negative predictive value for 83.3%, 55.6%, 55.6% and 83.3% respectively. While IT-rasio has sensitivity, specificity, positive and negative predictive value for 29.2%, 91.7%, 70% and 66%, respectively.Conclusion: NLCR has a satisfactory predictive value for neonatal sepsis that widely available and economic predictor alternative with cutoff point for 2.22.Keywords: NLCR, CRP, predictor, neonatal sepsisCorrespondence: Irfan Dzakir Nugroho. Masters Program in Family Medicine, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java.Indonesian Journal of Medicine (2021), 06(01): 112-118https://doi.org/10.26911/theijmed.2021.06.02.02